Effect of intravenous atropine on treadmill stress test results in patients with poor exercise capacity or chronotropic incompetence - Awad, Abdul ameer J. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: stress test (EST) is one of the main diagnostic and prognostic tests for ischemic heart disease. However, its usefulness depends on achieving target heart rate, then chronotropic incompetence and poor exercise capacity limits its utility. We evaluated the usefulness of atropine administration during the EST to decrease the number of tests with inconclusive results in these patients. Patients &Methods: We carried out this study in Ibn AI-Bitar Teaching Hospital from September 2007 to December 2008 and comprised of 210 patients undergoing EST. In subjects experiencing fatigue when they achieved 50-75% of target heart rate (THR), or those who failed to achieve their THR, atropine was administered in doses of 0.5 mg per minute until the test conclusion (positive test results or target heart rate achieved) or until a maximum dose of 2 mg was administered. Results: Forty-one (19.5%) of the 210 patients required atropine (mean dose: 1.1 mg) during the study. Among patients who received atropine, conclusive test was achieved in 38 cases (92.7%). Atropine administration resulted in a mean increase in heart rate of 38 beats/min (range 8-71 beat/min). Atropine injection resulted in a trend towards more positive results of EST in comparison to non-atropine group (31.7% versus 18.3%, /?=0.053). There was no difference in response to atropine in subjects with chronotropic incompetence or poor exercise capacity (p=0.5). Conclusion: Use of atropine as an adjunct to standard EST can help decrease the number of inconclusive tests. Larger studies are necessary to define the role of atropine in EST and also to evaluate the accuracy of conclusive EST after atropine administration